Natremia Significantly Influences the Clinical Outcomes in Patients with Severe Traumatic Brain Injury - Bharti Sharma; Winston Jiang; Munirah M. Hasan; George Agriantonis; Navin D. Bhatia; Zahra Shafaee; Kate Twelker; Jennifer Whittington (Diagnostics)
Objective: Fluctuations in sodium levels (SLs) may increase mortality, severity, and prolonged length of stay (LOS) in critically ill patients. We aim to study the effect of SL on various clinical outcomes in patients with severe traumatic brain injury (TBI). Methods: This is a single-center, retrospective study of patients with severe TBI from 1 January 2020 to 31 December 2023, inclusive. Patients were identified using Abbreviated Injury Severity (AIS) scores and International Classification of Diseases (ICD) injury descriptions. Result: Variations in hospital (H) admission SLs were statistically significant across four age ranges (pediatric, young adult, older adults, and elderly). Intensive care unit (ICU) admission, H discharge, and death also showed significance. A statistical difference was noted in ICU discharge levels while comparing blunt versus penetrating injury. We found statistically significant differences in SLs at H admission, ICU admission, and ICU discharge when compared to the Injury Severity Score (ISS) and the Glasgow Coma Scale (GCS) at admission. A linear regression analysis revealed a statistically significant positive correlation between ICU admission SLs and ISS. We discovered statistically significant differences when comparing ICU admission levels to H LOS, ventilator days, and mortality. Conclusions: SL upon ICU admission is correlated with ISS, GCS, and mortality rates. The elevated admission SL was linked to adverse hospital outcomes, including prolonged LOS at the H, ICU, and mechanical ventilation. Moreover, variability in serum SLs is independently associated with mortality throughout the hospital stay, irrespective of the absolute serum sodium concentration.